The Effect of Communication Overload, Information Overload, and Exhaustion on Student’s Learning Productivity - Sudarsono Putri, Shandra Elvyra; Aryo Pinandito (Faculty of Computer Science (FILKOM) Brawijaya University, 2024)
Every year, the percentage of Indonesians who utilize social media continues to increase. The ease of use of social media brings numerous advantages to users, particularly students. Students use social media to share and exchange learning materials, seek academic knowledge, and engage with friends and family. However, excessive use can cause exhaustion. This study aims to determine the ef- fect of overload factors on exhaustion and its effect on student learning productivity using linear regression analysis. Research data collection using questionnaires that obtain 100 respondents data. The research model uses the Stressor-Strain-Outcome (S-S-O) framework. The result suggested that communication overload affects student’s exhaustion, and student’s exhaustion also affects learning productivity.